EFFECTIVITY TEST OF RICE PHYLLOSPHERE BACTERIA AGAINST Xanthomonas Oryzae AND RESPON OF Streptomycin sulfate RESISTANCE - Elfidia Simanjuntak; Iman Suswanto; Tris Haris Ramadhan (Jurnal Sains Pertanian Equator, 2020)
Leaf blight is one of the crucial diseases caused by Xanthomonas oryzae pv.oryzae (Xoo) bacterial. Using of phyllosphere bacteria as biocontrol agents to againts Leaf |Blight disease has problem because can not to combination with synthetic bactericide applied. This study aims to determining potention of rice phyllosphere bacteria isolate against Xanthomonas oryzae pv.Oryzae caused of Leaf Blight Disease, and in vitro test Streptomycin sulfate resistance response. This research was conducted in Plant Disease Laboratory Faculty of Agriculture, University of Tanjungpura during 2 months. This study used 21 rice filosphere bacteria isolates. This research used paper disc method with concentrate levels 0 ppm, 50 ppm, 100 ppm, 250 ppm, 500 ppm. The result of this study showed that 6 isolates of rice filosphere bacteria have the potential to suppress the growth of Xanthomonas oryzae and are resistant to antibiotics (Streptomycin sulfate) up to 500 ppm. Key words: Leaf Blight Disease, biocontrol agent, phyllosphere, Resistance, Bactericide